An Android Application for Communication between Students and Faculty Members at the Faculty of Science, Zliten - Bakeer, Maruwan; Abead, Eyman; Saydoun, Abdulrahman (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Smartphones have become an integral part of modern human life, and many institutions, including universities and others, have rushed to use them to develop the educational process in all fields. The research is summarized in creating an Android application called Chat Sciences at the Faculty of Science, Zliten, which aims to benefit from students' use of mobile phones and their reliance on them in their daily lives. In addition, it aims to raise the status of the college scientifically in particular and the university in general, and also to enable students to quickly and easily access the information they need regarding study materials, exam dates, and others. The idea of ​​​​the research came, which is represented in creating an Android application for communication between students and faculty members to help them in the process of inquiring about information about their courses and the possibility of obtaining their grades, exam dates, and remedial lectures without the need to go to the college and inquire about them. Due to the clarity of the system requirements, the Waterfall Model methodology was used as an implementation model for the application, and the necessary data was collected from sources in college. The experimental approach was used to analyze the system using the Unified Modeling Language (UML). To design the system, a set of programming techniques were used, such as the Android Studio development environment, Flutter design technology, Dart programming language, and Firebase database. The application was tested to detect and address errors. The results of this research proved that the desired goals were achieved, as an effective system was built free of complexity. The research also reached a set of recommendations, the most important of which are: the possibility of adding a college link within the application with a link to the study and exam system.
Keywords: Mobile application; Students; Faculty Members; Inquiries; Student- Faculty members’ interaction